2017
DOI: 10.5152/tao.2017.2022
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Relationship between Umbilical Cord Blood Gas Values and Hearing Function in Neonates

Abstract: Objective: The aim of the present study was to examine the relationship between the results of the transient otoacoustic emission (TEOAE) test used in neonatal hearing screening and the results of the umbilical cord blood (UCB) analysis in neonates.Methods: This retrospective study included 209 neonates born in the obstetric unit at the 37 th gestational week. Based on the results of the TEOAE test, the neonates included in the study were divided into two groups as the study group composed of those "REFER" (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Durmus et al. did not find a difference in pH values of those who passed a transient otoacoustic emission test compared with those who had no response to a stimulus. In contrast, a previous study found an association between adverse acid‐base status and major sensorineural impairment in infants weighing less than 1000 g .…”
Section: Discussionmentioning
confidence: 94%
“…Durmus et al. did not find a difference in pH values of those who passed a transient otoacoustic emission test compared with those who had no response to a stimulus. In contrast, a previous study found an association between adverse acid‐base status and major sensorineural impairment in infants weighing less than 1000 g .…”
Section: Discussionmentioning
confidence: 94%